Progresses, Challenges, and Prospects of Genome Editing in Soybean (Glycine max) - Xu, Hu; Zhang, Lixiao; Zhang, Kang; Ran, Yidong (Frontiers in Plant Science, 2020)
Soybean (Glycine max (L.) Merr.) is a globally important crop for oil and protein source as food, feed and industrial raw material for biofuel. Genetic mediation including hybridization and transgenesis has led to increased productivity of soybean in the past century. Advances in genomics and emergence of multiple genome editing technologies through use of engineered site-speciﬁc nucleases (SSNs) have broaden the territory of plant science and agriculture. ZFNs, TALENS and CRISPR/Cas9 have been adapted in soybean improvement for targeted deletions, additions, replacements and corrections in the genome. The availability of reference genome assembly together with genomic resources increases feasibility to use current genome editing technologies as well as their new development. This review summarizes the current state in the use of the genome editing technology and predicts future directions the tool in soybean improvement.